The GATS Agreementon Financial Services : A Modest Start to Multilateral Liberalization - Sorsa, Piritta (IMF Working Papers; Working Paper ;, 1997)
This paper analyzes the links between multilateral, and unilateral financial liberalization, the former represented by the General Agreements on Trade in Services (GATS). It provides an overview of the main features of the GATS and what the participants in banking and securities within its framework, and compares GATS liberalization with the actual state of liberalization of the participants' financial sectors. The results suggest that in many countries multilaterally liberalized financial sector policies are more restrictive than the actual state of openness or development of financial sectors. Many emerging markets liberalized little under the GATS despite often well-developed financial markets, while the opposite was true in some less developed developing countries.